Urbanization and child malnutrition: A comparison of three countries in the Greater Mekong Sub-region - Thi Hoa Pahlisch; Priyanka Parvathi; Hermann Waibel (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2018)
Success in reducing monetary poverty in Southeast Asia has not fully translated into reduction in malnutrition. Using a two-year panel data from one province each in Thailand, Lao PDR and Vietnam, we study the correlation between monetary poverty and nutritional outcomes of children under five. Furthermore, we compare nutritional outcomes of children below five between rural and peri-urban areas. We apply ordinary least squares and district fixed-effects regressions and find that child nutrition remains a problem in rural areas across Southeast Asia despite achievements in poverty alleviation. Results reveal that although the households in the poorest quintile in both rural and peri-urban areas spend less on food; only the rural children are more likely to be stunted or underweight. It underscores the importance of investment in medical facilities near rural vicinities.
Keywords: O1; O18; I3; 330; Poverty; Child malnutrition; Peri-urban; Rural; Fixed-effects; Southeast Asia